THE RELATION BETWEEN WAITING TIME, FACILITY AVAILABILITY, AND HEALTHCARE WORKERS’ ATTITUDE ON PATIENT SATISFACTION IN PRIMARY HEALTHCARE FACILITIES IN CURUG, TANGERANG: A CROSS-SECTIONAL STUDY - Wahab, Fandy Varianto; Rampengan, Derren David; Tengor, Janeline R.S.; Kuluq, Marcellina Awing (Universitas Pelita Harapan, 2024)
Patient satisfaction is a crucial indicator of healthcare quality, particularly in primary healthcare facilities, where service efficiency and accessibility play a key role. This study focuses on analyzing the impact of waiting time, facility availability, and healthcare worker attitude on patient satisfaction at primary level healthcare facilities in Curug, Tangerang. A cross-sectional study was conducted using a Google Form questionnaire, collecting 373 responses from randomly selected patients (healthcare recipients). The results indicate that all three factors significantly influence patient satisfaction (physical facilities had a positive coefficient of 0.545, p = 0,000; service time showed a significant impact with a coefficient of 0.564, p = 0.000; healthcare worker’s attitude also had a coefficient of 0.564, p = 0.000). These findings emphasize the need for improved facility conditions, efficient service time management, and enhanced healthcare worker training to optimize patient satisfaction. Strengthening these areas in primary healthcare settings can enhance public trust and utilization of primary care services, ultimately contributing to overall public health improvement.